Discrimination of brownheart of Korla pear using vibration frequency spectrum technique - Hubo, Xu; Jie, Wu; Zhaopeng, Wang; Yongmao, Gao; Zhipeng, Wang; Zhengqiang, Zhao (International Journal of Agricultural and Biological Engineering, 2017)
The purpose of this work was to use a nondestructive method for detecting the brownheart of Korla pear to reduce the chance of infection among pears without brownheart. A mechanical impulse method based on vibration testing system was used to excite the fruits. The consistent acquisition signal indicated that the test is repeatable at the same positions of fruit equator (cheek). A remarkable frequency signal was excited at 9-12 N force by a rubber tipped hammer. The dominant frequency was identified at the maximum response magnitude to assess the internal defect, and the result was not influenced by the distances between the defect borders and the excitation points. The sharp increase of defect mass could significantly affect the dominant frequency. Relationship between the dominant response frequency (fd) and the defect mass percentage (ω) was characterized by an equation fd =410.649e-0.0833ω+261.947 with a good correlation coefficient (R2=0.925). A defect mass of 2.281% was determined as a discrimination threshold. Once the threshold exceeded 2.281%, the defective pear could be classified with a high accuracy rate of 96.7%. This finding would provide guidance for determining the optimal detecting time to the brownheart of Korla pears, according to the specific storage conditions when the vibration frequency spectrum method is deployed.Keywords: nondestructive detection, vibration frequency spectrum, brownheart of Korla pear, internal defect, fruit qualityDOI: 10.3965/j.ijabe.20171002.1910Citation: Xu H B, Wu J, Wang Z P, Gao Y M, Wang Z P, Zhao Z Q. Discrimination of brownheart of Korla pear using vibration frequency spectrum technique. Int J Agric & Biol Eng, 2017; 10(2): 259–266.